Population genetic structure of the bentfin devil ray (Mobula thurstoni) in the South Indonesia Sea with limited sample based on ND5 gene - ERICA DENISE WARDANA; I NYOMAN GIRI PUTRA; MUHAMMAD DANIE AL MALIK; NI LUH ASTRIA YUSMALINDA; ENEX YUNIARTI NINGSIH; NI PUTU DIAN PERTIWI; MUHAMMAD GHOZALY SALIM; MEUTHIA MAHARANI KANEDI; MOCHAMAD IQBAL HERWATA PUTRA; ANDRIANUS SEMBIRING (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wardana ED, Putra ING, Al Malik MD, Yusmalinda NLA, Ningsih EY, Pertiwi NPD, Salim MG, Kanedi MM, Putra MIH, Sembiring A. 2023. Population genetic structure of the bentfin devil ray (Mobula thurstoni) in the South Indonesia Sea with limited sample based on ND5 gene. Biodiversitas 24: 3743-3749. Bentfin devil ray (Mobula thurstoni) is one of five Mobula rays with a worldwide distribution. This species has high economic value and play an essential ecological role. However, due to their biological characteristics, such as low reproductive rates and late maturity, these species are highly vulnerable to overfishing and slow to recover from depletion. Genetic information, such as this species's population structure and genetic diversity is limited. This study aimed to determine the genetic variation and population structure of M. thurstoni in the South Indonesia Sea based on mitochondrial DNA from ND5 gene. Twenty-two samples of M. thurstoni were successfully collected from three locations Palabuhanratu (n=5), Muncar (n=13), and Savu Sea (n= 4). The haplotype diversity (Hd) ranged from 0.782 to 1.00 (mean=0.839), and Nucleotide diversity (?) ranged from 0.004 to 0.018 (mean=0.007). Then, no significant population differences (P-value > 0.05) were observed between locations, indicating that M. thurstoni population in the South Indonesian Sea represents a single genetic population. Additionally, the haplotype distribution also indicated the presence of two shared haplotypes between locations. Consequently, co-management strategies for sustainable fishing and conservation must be implemented across these three locations to ensure the sustainability of this species in the nature habitat.